Pelatihan Pengelolaan Keuangan Berbasis Komputer Dalam Peningkatan Tertib Administrasi Pada Kader Kesehatan Di Giwangan Umbulharjo Yogyakarta - Hiswati, Marselina Endah; Lestariningsih, Lestariningsih; Sapariyah, Sapariyah; Sudiyatmi, Sudiyatmi (Universitas Respati Yogyakarta, 2020)
PLKB health cadres in Giwangan Yogyakarta are now using conventional methods in accounting start from managing administrative data to financial processing. It requires manual documentation by writing on sheets of paper. Data loss due to paper based is vulnerable Apart from the possibility of unclear writing, tearing can cause damage on this document and cause problems that make it difficult for accountability. This paper applies the training method by giving lectures and computer demonstrations. The level of participant education requires a patient speaker in delivering the material in slowly and detail. Hence, the constraints required good, polite treatment, speech andwell ethics. The results of activity to the PLKB health cadre in Giwangan are expected to increase the understanding and give insight of computers beneficial in financial management. Besides, this activity can increase motivation in computerimplementation optimallyKeywords: PLKB cadres, financial management, training